Scaling F5 BIG-IP Load Balancer Automation: Enterprise-Grade Network Transformation Using Ansible and API-Driven Orchestration - Uday Kumar Soma (Malikussaleh University, Aceh, Indonesia, 2026)
Enterprise F5 BIG-IP load balancer estates, commonly spanning hundreds to thousands of Traffic Management Operating System devices across geographically distributed data centers, represent a class of infrastructure management challenge where the gap between manual operational capability and automation-required operational scale produces measurable security exposure, configuration drift risk, and delivery velocity constraint. This article presents the engineering principles, implementation architecture, and empirical outcomes of enterprise-scale F5 BIG-IP automation using Ansible and iControl REST API-driven orchestration, derived from the author's primary research in automating a 2,500-device production estate across aviation and financial services operational environments. The article addresses four critical automation engineering challenges: accurate dynamic inventory construction from multiple authoritative sources, pre-deployment dependency validation, preventing silent configuration failures, post-execution state verification, distinguishing reported success from actual convergence, and synchronization-aware orchestration for distributed Global Traffic Manager deployments through four production failure case studies whose analysis yielded architectural improvements now forming the operational standards. Performance outcomes from the author's enterprise deployments demonstrate estate-wide CVE remediation in 18 hours for a 2,500-device estate (versus a six-to-eight-week manual baseline), configuration change success rates of 98.4% with a 1.2% rollback rate across 847 production change executions, and zero-downtime software upgrades across High Availability device pairs using boot location management. The article further examines GitOps-based CI/CD integration, enabling application-speed F5 configuration changes through pull-request governance, artificial intelligence-driven predictive maintenance for anomaly detection before the incident threshold is crossed, and intent-based networking as a trajectory toward natural-language load-balancer policy management. The framework presented provides the engineering foundation for architecturally enabling autonomous network operations for routine load-balancer management tasks